Auxin Crosstalk with Reactive Oxygen and Nitrogen Species in Plant Development and Abiotic Stress. (7th October 2022) - Parveen, Nishat; Kandhol, Nidhi; Sharma, Shivesh; Singh, Vijay Pratap; Chauhan, Devendra Kumar; Ludwig-Müller, Jutta; Corpas, Francisco J; Tripathi, Durgesh Kumar
Abstract: The phytohormone auxin acts as an important signaling molecule having regulatory functions during the growth and development of plants. Reactive oxygen species (ROS) are also known to perform signaling functions at low concentrations; however, over-accumulation of ROS due to various environmental stresses damages the biomolecules and cell structures and leads to cell death, and therefore, it can be said that ROS act as a double-edged sword. Nitric oxide (NO), a gaseous signaling molecule, performs a wide range of favorable roles in plants. NO displays its positive role in photomorphogenesis, root growth, leaf expansion, seed germination, stomatal closure, senescence, fruit maturation, mitochondrial activity and metabolism of iron. Studies have revealed the early existence of these crucial molecules during evolution. Moreover, auxin, ROS and NO together show their involvement in various developmental processes and abiotic stress tolerance. Redox signaling is a primary response during exposure of plants to stresses and shows a link with auxin signaling. This review provides updated information related to crosstalk between auxin, ROS and NO starting from their evolution during early Earth periods and their interaction in plant growth and developmental processes as well as in the case of abiotic stresses to plants.